Tata Kelola dengan Prinsip Amanah, Adalah, dan Maslahah: Nilai-Nilai Hukum Islam dalam Pelayanan Publik Terpadu Satu Pintu Jakarta pada Era Otonomi Daerah - Muri; Otom Mustomi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study explores the implementation of the One-Stop Integrated Service (Pelayanan Terpadu Satu Pintu, PTSP) within the framework of regional autonomy, focusing on DKI Jakarta as both the administrative center and economic hub of Indonesia. Using a qualitative, library-based approach, the research examines the integration of Islamic legal principles—amanah (trustworthiness), adalah (justice), and maslahah (public benefit)—as normative and practical guidelines for governance. Findings show that these values reinforce good governance: amanah promotes honesty and accountability in the exercise of authority; adalah requires fairness and non-discrimination in service delivery; and maslahah directs policy toward collective welfare and harm prevention. The study concludes that embedding Islamic principles in PTSP governance enhances transparency, accountability, and equity, aligning administrative reform with the ethical imperatives of Islamic jurisprudence. Thus, PTSP can serve as a model that bridges legal, managerial, and moral-spiritual dimensions of public service.